THE PROBLEM OF THE SUPERVISION OF IMMIGRATION STAY LICENSES ON ILLEGAL FOREIGN LABOR WORKING IN FOREIGN CAPITAL INVESTMENT COMPANIES IN INDONESIA - Tony Mirwanto (Polteknik Imigrasi, 2018)
Abuse of Residence Permits by foreigners with the mode of using tourist visit visas often occurs, generally used in the context of working as a Foreign Worker in a Foreign Investment Company in Indonesia. This has led to a reduction in employment opportunities for Indonesian Migrant Workers in the country and a reduction in State income in terms of the use of Foreign Workers. Based on the facts in the field, the problem of misuse of Tourism Visit Stay Permits generally comes from the policy of Free Visa for Tourist Visits, this is a problem that over time is increasingly difficult to resolve, even more difficult to detect by law enforcement officials. The involvement of Indonesia in various international agreements that accommodate the ease of investment and the use of foreign labor, has made Indonesia increasingly fulfilled by investors and foreign workers. The problem of the use of foreign workers needs to be taken seriously by the government, especially in monitoring its activities while in Indonesia, so that the use of foreign labor can be beneficial for Indonesia. Giving ease of Visa Free in order to increase foreign exchange in tourism to foreigners who will enter Indonesia, of course, must be accompanied by supervision of their residence permit as a consequence of the ease of granting the Visa Free. In order for the practice of using foreign workers illegally by foreign investment companies, it can be minimized as early as possible